Ambivalence in Rejection Toward Rohingya Refugees in Aceh - Adami, Kodrat (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
The presence of rohingya refugees in Indonesia has been responded to by the community with rejection in recent years. This rejection has led to ambivalence in the attitudes directed towards the rohingya refugees. This research aims to answer how ambivalence occurs in the community's rejection of rohingya refugees in Sabang. This research was conducted qualitatively by combining social media discourse with interviews with the people of Sabang city. Data was collected through digital ethnography and semi-structured interviews to understand the dynamics of the community with refugees. The results showed that there has been ambivalence in the response to rohingya refugees in Sabang due to the discourse that developed in social media and in the community which is connected to the social and cultural conditions of the community. the conclusion of this study emphasizes the need for social cohesion, balanced presentation of actual information, and encouraging self-representation by refugees to avoid misrepresentation and conflict between the community and refugees. further research is recommended to explore the rejection that occurred in Aceh more broadly, as well as to make comparisons with cases outside Aceh that are also dealing with rohingya refugees.